Strategie międzynarodowej dywersyfikacji geograficznej a struktury własności polskich spółek publicznych - Bohdanowicz, Leszek; Jeżak, Jan; Matyjas, Zbigniew (International Geographical Diversification Strategies and Ownership Structure of Polish Public Companies, 2008)
In the article the authors describe the results of their research in the area of the relationship between ownership structure and the level of international geographical diversification of Polish public companies. The results of the research indicate that there is no correlation between these two groups of variables.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 39-46